Identification of MET10-932 and Characterization as an Allele Reducing Hydrogen Sulfide Formation in Wine Strains of Saccharomyces cerevisiae - Linderholm, Angela (American Society for Microbiology (ASM), 2010)
A vineyard isolate of the yeast Saccharomyces cerevisiae, UCD932, was identified as a strain producing little or no detectable hydrogen sulfide during wine fermentation. Genetic analysis revealed that this trait segregated as a single genetic determinant. The gene also conferred a white colony phenotype on BiGGY agar (bismuth-glucose-glycine-yeast agar), which is thought to indicate low basal levels of sulfite reductase activity. However, this isolate does not display a requirement for S-containing amino acids, indicating that the sulfate reduction pathway is fully operational. Genetic crosses against known mutations conferring white colony color on BiGGY agar identified the gene leading to reduced H(2)S formation as an allele of MET10 (MET10-932), which encodes a catalytic subunit of sulfite reductase. Sequence analysis of MET10-932 revealed several corresponding amino acid differences in relation to laboratory strain S288C. Allele differences for other genes of the sulfate reduction pathway were also detected in UCD932. The MET10 allele of UCD932 was found to be unique in comparison to the sequences of several other vineyard isolates with differing levels of production of H(2)S. Replacing the MET10 allele of high-H(2)S-producing strains with MET10-932 prevented H(2)S formation by those strains. A single mutative change, corresponding to T662K, in MET10-932 resulted in a loss of H(2)S production. The role of site 662 in sulfide reduction was further analyzed by changing the encoded amino acid at this position. A change back to threonine or to the conservative serine fully restored the H(2)S formation conferred by this allele. In addition to T662K, arginine, tryptophan, and glutamic acid substitutions similarly reduced sulfide formation.